Imaging neuron-glia interactions in the enteric nervous system - Boesmans, Werend; Martens, Michiel A.; Weltens, Nathalie; Hao, Marlene M.; Tack, Jan; Cirillo, Carla; Vanden Berghe, Pieter (Frontiers in Cellular Neuroscience, 2013)
The enteric nervous system (ENS) is a network of neurons and glia within the wall of the gastrointestinal tract that is able to control many aspects of digestive function independently from the central nervous system. Enteric glial cells share several features with astrocytes and are closely associated with enteric neurons and their processes both within enteric ganglia, and along interconnecting fiber bundles. Similar to other parts of the nervous system, there is communication between enteric neurons and glia; enteric glial cells can detect neuronal activity and have the machinery to intermediate neurotransmission. However, due to the close contact between these two cell types and the particular characteristics of the gut wall, the recording of enteric glial cell activity in live imaging experiments, especially in the context of their interaction with neurons, is not straightforward. Most studies have used calcium imaging approaches to examine enteric glial cell activity but in many cases, it is difficult to distinguish whether observed transients arise from glial cells, or neuronal processes or varicosities in their vicinity. In this technical report, we describe a number of approaches to unravel the complex neuron-glia crosstalk in the ENS, focusing on the challenges and possibilities of live microscopic imaging in both animal models and human tissue samples.